Superoxide Dismutases in Immune Regulation and Infectious Diseases - Tong Liu; Jiajin Shang; Qijun Chen (Antioxidants)
Superoxide dismutases (SODs) maintain redox homeostasis through the catalytic dismutation of superoxide anions, thereby affording protection to organisms against oxidative damage. The SOD family, encompassing Cu/Zn-SOD, Mn-SOD, Fe-SOD, and Ni-SOD, exhibits structural diversity and constitutes a multilevel antioxidant defense system with discrete subcellular localizations. Beyond their antioxidant functions, SODs also function as immunomodulatory proteins, regulating the maturation, proliferation, and differentiation of immune cells. They further fulfill a crucial role in host responses to parasitic infections. The current review synthesizes and critically evaluates extant research to comprehensively delineate the molecular architecture of SODs, their intricate post-translational modification (PTM) networks, and their dual regulatory mechanisms at the interface of immunomodulation and pathological processes. This review establishes a critical framework for elucidating the biological significance of redox homeostasis maintenance.